Repeated Neurological Complications during Dialysis – A Case for Echo?. Issue 1 (9th November 2013) - Groves, Danja S.; Harding, Ulf; Lanckohr, Christian; Gottschalk, Antje; Kern, John A.; Schmidt, Christoph
Mini‐Abstract A 65‐year old woman presented with acute or chronic renal failure and signs of right heart failure. Renal replacement therapy—using a surgically placed dialysis catheter via the left jugular vein—was repeatedly complicated by altered flows of the dialysis unit, impaired consciousness, new onset of seizures and left‐sided hemiparesis. The tip of the dialysis catheter was detected on transesophageal echocardiography within the lumen of the ascending aorta. Further imaging of the neck vessels demonstrated a primary placement of the catheter in the left common carotid artery. This incident underscores the value of ultrasound guidance for placement of intravascular catheters.